German-Iowan Strategies in Celebrating the Centennial of Alexander von Humboldt’s Birth - Roba, Bill (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2014)
The two largest cities of Eastern Iowa on the shore of the Mississippi River are Dubuque and Davenport. In each city, an elite group of German-Iowan leaders emerged by the late 1850s. Bill Roba describes and examines their strategies in celebrating the Centennial of Alexander von Humboldt’s Birth.